14 SUBTELOMERIC DNA PROBE ANALYSIS INCREASES DIAGNOSTIC YIELD IN DYSMORPHIC PATIENTS WITH COGNITIVE IMPAIRMENT. Issue 1 (1st January 2007) - Huang, P.; Bay, C.; Cottrill, C.
Abstract : The subtelomeric region of chromosomes has been identified as having a large number of important genes that when deleted are associated with significant impairments. Recent advances in the technology associated with genetic evaluation of subtelomeric regions of chromosomes in patients with dysmorphic features and cognitive impairment have greatly increased the diagnostic yield. Meta-analyses of multiple outcome studies have demonstrated that the increased diagnostic yield of subtelomeric DNA probes approaches 5 to 6%. Thus, the ability to provide an answer to clinicians and families has dramatically improved. This new technology also provides the basis of more precise genetic counseling for future pregnancies. We present four cases in three families of individuals who were recently diagnosed with an abnormal karyotype using subtelomere DNA probes, who in previous evaluations had been diagnosed as an unknown multiple anomaly syndrome with no etiology identified. Previous karyotypes were normal in all cases. Family 1 consists of two siblings with a small unbalanced rearrangement of chromosomes 13 and 18. Both siblings effectively had a partial trisomy of chromosome 13 and monosomy of 18. The older child had rocker-bottom feet, dysmorphic facial features, and autistic behaviors and developmental delays. The newborn sibling has rocker-bottom feet and tetralogy of Fallot. The rearrangements were not identified in routine karyotypes. Parental testing identified one parent as being a balanced carrier. Cases 3 and 4 have deletions of 1p36 and 3q29, respectively. Their cases will be presented.